G655 Development of a formal clinical supervision policy for ADHD specialist nurses working in a child development centre. (May 2019) - Ozer, S; Takon, I; Atherton, M; Beets, R
Abstract : Introduction: Clinical Supervision is a formal process of professional support and learning enabling individual practitioners to develop knowledge and competence assume responsibility for their own practice and enhance consumer protection and safety of care in complex clinical situations. Following a CQC inspection of our Trust, poor documentation of nursing competencies was highlighted in their report. It is recommended by the Care Quality Commission (CQC) that in services for people with a learning disability or autism, staff caring for the people using the services should have access to appropriate forms of support including Clinical supervision.² Aim/objectives: Provide a safe and confidential environment for ADHD nurse to reflect on and discuss their work and personal and professional responses to their work. Support ADHD Nurse Specialists in their personal and professional development and in reflecting on their practice. Facilitate new learning opportunities, identify training needs and ensure availability of ADHD and neurodevelopmental related CPD opportunities for continuous improvement. Support elements of clinical governance including quality improvement and risk management. Methodology: ADHD Lead Clinicians engaged over a 3 month period (April- June 2018) with the Lead nurses in Acute/Community Paediatrics and ADHD Nurse Specialists to review the CQC recommendation above and explore the need for a formal clinical supervision protocol that could be replicated across other Nurse Specialist areas. ADHD Lead Clinicians also reviewed academic literature on the benefits of clinical supervision incorporating this into the discussions with lead nurses and final document. Following discussions, the purpose, scope of supervision and expectations for effective and successful supervision were agreed and documented in the policy. The final document was ratified by the Trust's quality and patient safety committee and then circulated to the Team. Results: The ratified clinical supervision policy includes an agreement between the supervisees (ADHD Nurse Specialists) and clinical supervisors (ADHD Lead Clinicians). Date, time and frequency of the supervision event are clearly documented in the policy. Agenda items circulated ahead of the supervision meeting include clinical/prescribing issues, leadership, clinical governance, learning, teaching and support. The supervisee (ADHD Nurse) is expected to record all discussions and make this available to their line manager. Clinical supervisors (ADHD Lead Clinicians) and ADHD Nurse Specialists are expected to ensure all agreed goals and actions are SMART. The first supervision meeting was rated very useful by the Specialist nurses Conclusion: Following the development of the clinical supervision protocol, work is in progress to develop the first formal national clinical supervision competency framework for ADHD Nurses. The clinical supervision protocol has also been adopted by other specialist nursing areas locally.